Early onset of menopause is associated with increased peripheral atherosclerotic plaque volume and progression. (March 2020) - Schreinlechner, Michael; Noflatscher, Maria; Reinstadler, Sebastian Johannes; Sommer, Philip; Lener, Daniela; Reiser, Elisabeth; Theurl, Markus; Kirchmair, Rudolf; Bauer, Axel; Marschang, Peter
Abstract: Background and aims: Cardiovascular disease (CVD) is the leading cause of death in western countries. One risk factor unique to women is the menopausal status. The aim of this study was to analyse the influence of the onset of menopause (MP) on the extent and progression of atherosclerotic plaque volume (PV). Methods: Postmenopausal women with at least one cardiovascular risk factor (CVRF) but without established CVD were included. Quantification of PV was performed in peripheral arteries using a three - dimensional (3D) ultrasound (US) technique. Follow-up examination to assess PV progression was performed after 19 (±8) months. Results: 110 consecutive postmenopausal women (mean age 65.5) were included. Females with an earlier onset of MP (<45 years) had a significantly higher PV than those with an intermediate (45–52 years) or later onset of menopause (>52 years), irrespective of other CVRF (244 mm³ vs. 193 mm³ vs. 73 mm³, respectively, p = 0.023). In addition, women with an earlier onset of MP had a higher PV progression compared to women with an intermediate or late onset (40 mm³ vs. 35 mm³ vs. 8.5 mm³; p = 0.002, respectively). Moreover, these results were confirmed in multivariate regression, where only onset of MP (OR 0.88; 95%CI 0.81–0.96; p = 0.004) and age (OR 1.06; 95%CI 1.08–1.13; p = 0.025) were significant predictors for a higher atherosclerotic progression. Conclusions: An earlier onset of MP was associated with an increase in atherosclerotic PV and accelerated progression, independent of other CVRF. Graphical abstract: Image 1 Highlights: Earlier menopause (MP) was associated with higher atherosclerotic plaque volume & accelerated atherosclerotic progression. Risk stratification for postmenopausal women may be improved by additional anamnestic questions evaluating the onset of MP. In females with an earlier onset of MP an adapted strategy to control risk factors more aggressively may be considered. Therefore, we suggest the onset of MP as a risk factor unique to women.